INCLUSIVITY IN SOCIAL MEDIA ADVERTISING: WAY AHEAD FOR BRANDS - Joon, Neeru; Hooda, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
India is one of the most populous and diverse countries in the world. Its diversity is reflected by hundreds of languages spoken, tribes, religions, ethnicities, cultures, and social structures across the population of over one billion. Advertisements on social media platforms like Instagram have provided massive opportunities for today’s dynamic businesses to collaborate and develop strong networks with diverse target customers. This diversity could be very beneficial for India’s development and growth. But lack of inclusivity in advertising is a long-standing problem in India. Despite growing awareness, many minorities remain under or inappropriately represented. In managing brands and targeting consumers, advertising must understand and contend with India’s social and cultural diversity. The content published on the social platform should be diverse and inclusive of all sections of society because people want to see themselves represented in advertisements. However, if an advertiser fails to maximize inclusion by ignoring the fact that every brand and community are different, then they will also fail to maximize their campaign’s reach because brands that are inclusive in their marketing are viewed as more authentic and trustworthy. The purpose here is to discuss the different ways in which brands can successfully follow an Inclusive Approach. Being truly comprehensive on social media means finding ways to make gender, race, ethnicity, and age-inclusive content. Hence, the rise in inclusivity in Social Media Advertisements is the way ahead for the success of brands.